1993
DOI: 10.1007/bf00341270
|View full text |Cite
|
Sign up to set email alerts
|

The NSAID sulindac reverses rectal adenomas in colectomized patients with familial adenomatous polyposis: clinical results of a dose-finding study on rectal sulindac administration

Abstract: After colectomy with ileorectal anastomosis (IRA) for treatment of familial adenomatous polyposis (FAP), the rectal mucosa remains, with the risk of malignant change. Locoregional (rectal) sulindac has been applied, with initial higher-dose therapy and subsequent low-dose maintenance therapy to minimise side-effects. The dose-finding study with sulindac suppositories started with a dose of 300 mg sulindac daily per patient over 6 weeks. Depending on proctoscopical evaluation of regression of polyposis, sulinda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(32 citation statements)
references
References 26 publications
0
30
0
2
Order By: Relevance
“…This suggests that multiple apoptotic controls exist to control neoplasia in long-lived organisms such as the human. In colorectal mucosa, the first apoptotic control point appears to be mediated by APC, while a reserve system, (38)(39)(40)(41)(42). Because colorectal tumor cells lack intact APC, it was suggested that these NSAIDs replace a physiologic function of APC that was abrogated by mutation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that multiple apoptotic controls exist to control neoplasia in long-lived organisms such as the human. In colorectal mucosa, the first apoptotic control point appears to be mediated by APC, while a reserve system, (38)(39)(40)(41)(42). Because colorectal tumor cells lack intact APC, it was suggested that these NSAIDs replace a physiologic function of APC that was abrogated by mutation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mode of action responsible for these effects is poorly understood. NSAIDs are potent inhibitors of Cox, the enzyme responsible for the formation of prostaglandins from arachidonic acid, and are used to treat familial adenomatous polyposis, a genetic disorder resulting in abnormal colorectal polyp formation, in humans (12). Until recently, the mode of action of NSAID was thought to be solely through inhibition of Cox, which, along with its products such as prostaglandin E 2 , is up-regulated in tumors and enhances the invasion of cancer cells via matrix metalloproteinase-2 (MMP-2; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Sulindac sulfide inhibits the growth of tumor cells in soft agar (13,14), inhibits the growth of tumors in xenograft mouse models (14,15), and is a effective stimulator of apoptosis under a number of experimental conditions (8, 16 -22). In addition, sulindac and, hence, its metabolite, sulindac sulfide, are currently used to suppress the development of adenomatous polyps in patients with familial adenomatous polyposis (23). However, understanding the mechanisms responsible for the anti-tumorigenic activity of sulindac sulfide and other NSAIDs is lacking.…”
mentioning
confidence: 99%